The Good, the Bad and the Ugly: the representations of O Estado de São Paulo newspaper about the three main presidential candidates in the 1989 elections - da Luz, Thaíze Ferreira (Revista Crítica Histórica, 2020)
This article proposes to analyze of the representation of political figures in the print media. From the point of view of representations, newspapers are able to provide information not only about society but also about the constitution of the social. The objective of this paper is to verify how the construction of the image of the three main presidential candidates of 1989, Fernando Collor de Mello, Leonel Brizola and Luiz Inácio Lula da Silva, was made by the newspaper O Estado de São Paulo and how these representations elaborate a symbolic construction of these candidates. For such, it was observed the use of the images in the pages of O Estado de São Paulo and the discursive construction of the periodical, in the same edition.